No-shows among female patients aged 18-35 - Sobolewska, Magdalena; Miros, Magdalena; Olejniczak, Dominik (Journal of Education, Health and Sport, 2019)
Introduction. Patients’ failure to keep medical appointments or to cancel them is becoming an increasing problem for the health care system. The phenomenon of missing medical appointments refers to patients of both public and private healthcare facilities. It has a negative impact on the functioning of the health care system, by contributing to longer waiting times for health services and generating financial losses. Aim. The aim of the study was to analyze no-shows in female patients aged 18-35. Material and method. The research tool used in the study was a survey that was conducted among 705 women aged 18-35. The survey questionnaire had been developed by the authors of the study and consisted of particulars and five thematic areas. The first area concerned cancellation of medical appointments and the reasons behind it. In the second area, patients’ punctuality was assessed. The third area focused on preferred methods of arranging and cancelling medical appointments. In the fourth area, women’s opinion on the idea of spreading lists of negligent patients among medical facilities was examined. The fifth area referred to patients’ solutions to the problem of not keeping medical appointments. The obtained data was subjected to statistical analysis using the ² test, where p < 0.05 was considered to be a statistically significant. Results. The study shows that nearly 75% of women have canceled their medical appointment at least once. The phenomenon of not keeping appointments and not cancelling them concerned in particular women aged 29-35 (33%). In each of the three age groups, the most frequent reasons for not attending an appointment and not cancelling it were forgetfulness, recovery from a health condition, other more important errands and personal situation. Over a quarter of respondents declared having been late for an appointment at least once (28%). Nearly half of the respondents inform medical facilities about the fact of being late (46%). Conclusions. It is necessary to monitor patients’ failure to keep medical appointments, introduce a general system of reminding patients about medical appointments and educate patients about the obligation to inform medical facilities about cancelling appointments.